O-033 Radiation savings in pediatric angiographic procedures by incorporation of extra-low dose settings into procedure time-out. (12th July 2011) - Morris, P
Abstract : Background: With the introduction of the Artis Zee Siemens biplane neuroangiographic suite into our department, radiation exposure and skin-dose estimates were collected prospectively on all pediatric procedures using ultra-low exposure settings beyond those recommended by the manufacturer. Pediatric "Minus" settings for fluoroscopy were set at 3 fps and 18 nGy/p (default 7.5–10 fps and 23 nGy/p). Setting this low-dose protocol was incorporated into our pre-procedure "Timeout" to assure compliance. Methods: Estimates of radiation dose were reviewed for 10 consecutive diagnostic and 10 interventional pediatric procedures. These results were compared with exposure parameters recorded using fluoroscopy and DSA with an adult size phantom using our pediatric low dose, the manufacturer's recommended pediatric settings, our adult low dose protocol, and the manufacturer's default adult settings. Results: Estimated skin dose per case varied from 45.1 to 1888 mGy and Dose-Area-Product (DAP) varied from 27.2 to 5426 microGym 2 . The lower tier of exposures were all diagnostic procedures. For diagnostic procedures fluoroscopy related DAP readings accounted for 1.7–11.5% of the total DAP reading, and fluoroscopy accounted for 1–17% of the total estimated skin dose. For embolization procedures fluoroscopy accounted for 19–55.6% of DAP readings, and for 20–58% of estimated skin dose. Phantom DAP readings and estimated skin dose using a gamut of protocols suggest that fluoroscopy radiation readings using our pediatric minus protocol represent a dose savings of up to 88% compared with using an adult manufacturer's default setting at 7.5 fps at similar magnification. Phantom runs of DSA using Pediatric and Adult settings estimated a radiation dose reduction of at least 75% in DAP readings and 65% in skin dose compared with manufacturer adult default settings. Conclusion: Physician compliance with use of lower-dose pediatric radiation protocols for neuroangiographic procedures has the potential to result in substantial reduction of patient dose compared with likely doses accrued through inadvertent conduct of the case in default or adult settings. Fluorocopy settings are proportionately a larger component of the total dose during interventional procedures, underscoring the importance of compliance with manual fixing of protocol settings at the beginning of each case.